2021
DOI: 10.1007/s12517-021-08676-x
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic assessment method on collapse risk of small spacing tunnels based on attribute interval recognition model

Abstract: Due to the small thickness of the middle rock wall, the complex surrounding rock stress, and the great influence of construction, the large deformation and even the collapse of the vault are easy to occur in the small spacing tunnel. In order to more accurately assess the risk caused by tunnel collapse, combining with the case of a small spacing tunnel in the Puyan Highway in Fujian province, the evaluation index system and classification standard of tunnel collapse risk assessment were established based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In order to comprehensively analyze the risk situation of mountain tunnels, this paper obtains categories [10][11][12][13][14] based on the relevant industry standards and the existing research results, as shown in Table 1. Deng first proposed the D-number theory [15], which is extended and extended in DS evidence theory.…”
Section: Classification Standard For Risk Collapse Of Mountain Tunnelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to comprehensively analyze the risk situation of mountain tunnels, this paper obtains categories [10][11][12][13][14] based on the relevant industry standards and the existing research results, as shown in Table 1. Deng first proposed the D-number theory [15], which is extended and extended in DS evidence theory.…”
Section: Classification Standard For Risk Collapse Of Mountain Tunnelsmentioning
confidence: 99%
“…Step 6: The index weights were calculated from the matrix R T c1 . Inconsistency coefficient test is performed by Formulas ( 9) and (10):…”
Section: D-ahp Theorymentioning
confidence: 99%